Effect of Defoliation at Different Stages on Grain Sorghum Yield and Yield Components in 2024 - Kraig L. Roozeboom (Kansas Agricultural Experiment Station Research Reports, 2025)
A third year of an experiment to quantify yield reductions associated with various levels of defoliation imposed at different stages of grain sorghum development was conducted at Manhattan, KS, in 2024. Target defoliations of 0, 33%, 66%, and 100% were imposed at 5-leaf, flag leaf appearance, half bloom, and hard dough stages. Defoliation of 5-leaf sorghum resulted in minimal yield loss unless the defoliation rate was 100%, which also delayed heading. Yield reductions were greatest when leaf area was lost at flag leaf appearance or half bloom. Leaf area loss of 60% or greater at these stages caused yield losses of 30% to 70%. Leaf area losses approaching 100% at the early hard dough stage caused yield reductions approaching 30%. Yield losses were associated with different combinations of reductions in head size and seed size depending on timing of leaf loss.
Keywords: grain sorghum; defoliation; yield; yield components; developmental stages